Peran Budaya Perusahaan dalam Mewujudkan Iklim Kerja Inklusif: Penguatan Kepemimpinan sebagai Penggerak Perubahan Organisasi - Aziza, Pretty (ANTASENA: Governance and Innovation Journal, 2025)
Corporate culture plays a critical role in shaping employees’ interactions, behaviors, and work experiences; however, limited research has examined how culture itself can be utilized as a strategic instrument to cultivate an inclusive work climate. This gap persists because most studies position DEI initiatives as the drivers of cultural change rather than viewing culture as the foundation that enables inclusivity. This study aims to analyze the role of corporate culture in creating an inclusive work climate by emphasizing leadership strengthening as a key determinant. A Systematic Literature Review (SLR) was conducted using recent studies on inclusive leadership, organizational culture, DEI implementation, and workplace climate. The analysis involved identifying, selecting, and synthesizing relevant literature to derive an integrated conceptual pattern. The findings indicate that inclusive leadership drives the development of a culture that promotes openness, fairness, and collaboration, which subsequently fosters an inclusive work climate through psychological safety, employee engagement, and perceptions of justice. DEI programs and practices further reinforce this process by providing institutional mechanisms for embedding cultural values. In conclusion, corporate culture can be operationalized as a strategic instrument for building an inclusive work climate, with leadership serving as the primary catalyst for organizational transformation.